2022
DOI: 10.1080/13880209.2022.2080234
|View full text |Cite
|
Sign up to set email alerts
|

S -Propargyl-cysteine prevents concanavalin A-induced immunological liver injury in mice

Abstract: Context S -Propargyl-cysteine (SPRC), an endogenous H 2 S modulator, exerts anti-inflammatory effects on cardiovascular and neurodegenerative disease, but it remains unknown whether SPRC can prevent autoimmune hepatitis. Objective To evaluate the preventive effect of SPRC on concanavalin A (Con A)-induced liver injury and uncover the underlying mechanisms. Materials and methods Mice were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Following Con-A injection, Kupffer cells and T cells are greatly activated and infiltered in hepatic tissue causing immunological liver damage [ 7 , 41 , 42 ]. These cells over-secrete ROS, ILs, and TNF-α which binds to TNF- receptor-1 existing in the hepatocytes, leading to the activation of various signal transduction-linked proteins such as JNK that modulates the survival or death of hepatocytes during the inflammatory reaction [ 50 ]. An earlier study has shown that JNK-deficient mice are resistant to Con-A-caused hepatitis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following Con-A injection, Kupffer cells and T cells are greatly activated and infiltered in hepatic tissue causing immunological liver damage [ 7 , 41 , 42 ]. These cells over-secrete ROS, ILs, and TNF-α which binds to TNF- receptor-1 existing in the hepatocytes, leading to the activation of various signal transduction-linked proteins such as JNK that modulates the survival or death of hepatocytes during the inflammatory reaction [ 50 ]. An earlier study has shown that JNK-deficient mice are resistant to Con-A-caused hepatitis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the level of S-adenosylmethionine (AdoMet) in the brains of patients was 0.18 ± 0.04 nmol/mg, which was much lower than the normal level of 0.52 ± 0.07 nmol/mg. This was due to the low level of AdoMet in the brains of AD patients, which affected CBS activity and thus reduced the synthesis of H 2 S. In a severe AD model, H 2 S supply reduced Ab deposition, hyperphosphorylation of p-APP (the precursor protein of Ab) and Tau isoforms, and the inflammatory response to improve cognitive activity (52). This provides a new idea for the mechanism of the protective effect of H 2 S on AD.…”
Section: Gas Signaling Molecules and Alzheimer's Diseasementioning
confidence: 98%
“…H 2 S's therapeutic potential for respiratory disorders has recently attracted a lot of attention. In obstructive respiratory illness, pulmonary fibrosis, emphysema, pancreatic inflammatory/respiratory lung damage [ 10 ], liver inflammation [ 11 ], diabetic cardiomyopathy [ 12 ], and anti-cancer [ 13 ], H 2 S is an essential treatment component. We anticipated that H 2 S may modulate ROS formation, as well as metalloproteinases and adhesion molecule expression responses, MAP kinase signaling, and the release and attraction of inflammatory mediators in BPA-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%